Determinants of Financial Distress: The Role of Operating Capacity, Sales Growth, Operating Cash Flow, and Leverage - Maulidina, Azizah; Purwidianti, Wida; Tubastuvi, Naelati; Alfalisyado, Alfalisyado (Akuisisi : Jurnal Akuntansi, 2025)
This research examines the influence of operating capacity, sales growth, operating cash flow, and leverage on the financial distress conditions of companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2020-2022. This study uses a purposive sampling method for sampling with a sample size of 57 companies. The analysis technique used is binary logistic regression using SPSS version 26. The results of this study indicate that operating capacity and leverage have a significant effect on the company's financial distress, while sales growth and operating cash flow have no significant effect on the company's financial distress.